Banyu Lemon Sales Management Based on Information and Technology - Edy Susena; Suci Purwandari; Markus Sukendar; Riyan Setiyanto (Politeknik Negeri Madiun, 2023)
Technology was created to facilitate activities in everyday life, and to help us provide fast, precise, and accurate information. The internet is not only a communication tool for spreading information that is very fast and cheap. In the economic field there are many marketing methods via the internet to achieve increased sales turnover targets. An e-commerce website or online store is a website that aims to sell one or more goods and services using electronic media as a medium for information and transaction media for these goods/services. Before getting to know the internet, the sellers only advertised the company through word of mouth and distribution of brochures so that only a few people knew about it. Currently, Banyu Lemon does not yet have publicity or promotion facilities, so that consumers who visit Banyu Lemon are only from the surrounding area and people outside the area do not know the existence and products of the shop. Meanwhile, in promotion we need a media that can help the promotion reach the target consumers. Therefore, in order to provide good service to consumers while promoting Banyu Lemon products, an information media in the form of a website is designed to promote and increase sales of Banyu Lemon products.